Analisis Konservasi Energi Dalam Sistem Fisika - Hia, Nicholas Kurniawan; Hulu, Operius (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2024)
Energy conservation is a fundamental principle in physics, stating that energy cannot be created or destroyed, but only transformed from one form to another. This principle plays a crucial role in modern technologies, particularly in the renewable energy sector and efforts to enhance energy efficiency. This research analyzes literature related to the application of energy conservation in various physical systems, including renewable energy technologies such as solar and wind power, as well as thermal and mechanical systems. The findings indicate that although significant progress has been made in implementing energy conservation, major challenges such as high initial infrastructure costs and energy storage efficiency remain obstacles. This study also highlights the importance of government policies in supporting innovation in renewable energy and energy efficiency for the future. It is hoped that this research will contribute to the development of more efficient and environmentally friendly energy solutions.